#### Answer

-x - 7

#### Work Step by Step

($x^{2}$ - 49) / (7 - x) = (x - 7)(x + 7) / (-1)(x - 7) = (x + 7) / (-1) = -x - 7

Published by
Pearson

ISBN 10:
0321785045

ISBN 13:
978-0-32178-504-6

-x - 7

($x^{2}$ - 49) / (7 - x) = (x - 7)(x + 7) / (-1)(x - 7) = (x + 7) / (-1) = -x - 7

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.